The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1029/1999gb001245
|View full text |Cite
|
Sign up to set email alerts
|

Paleoclimate and vegetation of the Last Glacial Cycles in Jerusalem from a Speleothem Record

Abstract: Abstract. A speleothem isotopic record taken from Jerusalem is used to reconstruct regional climate over the last 170,000 years. Glacial periods in Jerusalem were generally cooler and wetter than the present climate. Stage 5e in the desert margin of Jerusalem was extremely unstable, dry, and warm, and instability persisted throughout the transition to glacial conditions. The climate after stage 5e became gradually cooler and wetter over a 20,000-year interval and did not recover to interglacial conditions in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 34 publications
3
78
0
1
Order By: Relevance
“…Speleothem sample 2N provides a relevant record of both regional-and hemisphere-scale climate responses to deglaciation . The existing d 18 O record from Soreq Cave generally agrees with that of other speleothems in the region (Frumkin et al, 2000;Verheyden et al, 2008). Soreq Cave is located such that it is influenced by the eastward advection of complex climatic variability in the North Atlantic.…”
Section: Related Environmental Proxy Recordssupporting
confidence: 55%
“…Speleothem sample 2N provides a relevant record of both regional-and hemisphere-scale climate responses to deglaciation . The existing d 18 O record from Soreq Cave generally agrees with that of other speleothems in the region (Frumkin et al, 2000;Verheyden et al, 2008). Soreq Cave is located such that it is influenced by the eastward advection of complex climatic variability in the North Atlantic.…”
Section: Related Environmental Proxy Recordssupporting
confidence: 55%
“…They also estimated that rainfall ranged from 550 to 700 mm/a during the early Holocene (8-7.5 ka BP). The speleothem 13 C record from the Jerusalem West Cave shows a negative excursion during the early Holocene, compared to heavier values in the late Pleistocene or in the late Holocene, suggesting more C 3 vegetation and higher rainfall (Frumkin et al, 2000). Emeis et al (1998Emeis et al ( , 2000Emeis et al ( , 2003 suggested that the Eastern Mediterranean was characterised by rising temperatures and lower salinities in the early Holocene due to increased freshwater input.…”
Section: Palaeoclimatolgymentioning
confidence: 98%
“…Recent studies address the region's climatic Machlus et al, 2000;Abed and Yaghan, 2000;Stein, 2001;Bartov et al, 2002Bartov et al, , 2003Landmann et al, 2002), seismic (Marco et al, 1996), and paleomagnetic history (Marco et al, 1998). A precise chronology is the foundation of all of these studies, as well as the basis for comparison to other regional climate archives such as speleothems (Bar-Matthews et al, 1997Kaufman et al, 1998;Matthews et al, 2000;Frumkin et al, 1999Frumkin et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%